2014
DOI: 10.7314/apjcp.2014.15.18.7947
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Factors and Risk of Pancreatic Cancer: a Multi-Centre Case-Control Study in China

Abstract: Background: Pancreatic cancer is the sixth leading cause of cancer death with an increasing trend in China. Dietary intake is believed to play an important role in pancreatic cancer carcinogenesis. The aim of this paper was to evaluate associations between some dietary factors and risk of pancreatic cancer in a multi-centre case-control study conducted in China. Materials and Methods: Cases (n=323) were ascertained from four provincial cancer hospitals. Controls (n=323) were randomly selected from the family m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The prognosis of patients with advanced stage pancreatic cancer is much worse than for those with early stage disease. Unfortunately, more than 80% of pancreatic cancer patients were in an advanced stage when diagnosed (Huang et al, 2009;Liu et al, 2014) U r i d i n e 5 ' -d i p h o s p h a t e ( U D P ) -glucuronosyltransferases (UGTs) are an important group of phase II drug metabolism enzymes in humans (Tukey and Strassburg, 2000). The human UDPglucuronosyltransferases (UGTs) are a superfamily ofThe UGT enzymes have been divided into two families of proteins termed UGT1 and UGT2, and three subfamilies of proteins termed UGT1A, UGT2A and UGT2B in human beings (Hanioka et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of patients with advanced stage pancreatic cancer is much worse than for those with early stage disease. Unfortunately, more than 80% of pancreatic cancer patients were in an advanced stage when diagnosed (Huang et al, 2009;Liu et al, 2014) U r i d i n e 5 ' -d i p h o s p h a t e ( U D P ) -glucuronosyltransferases (UGTs) are an important group of phase II drug metabolism enzymes in humans (Tukey and Strassburg, 2000). The human UDPglucuronosyltransferases (UGTs) are a superfamily ofThe UGT enzymes have been divided into two families of proteins termed UGT1 and UGT2, and three subfamilies of proteins termed UGT1A, UGT2A and UGT2B in human beings (Hanioka et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In previous cohort studies, no association was found between fruit and vegetable intake and pancreatic cancer risk . However, several case–control studies have suggested an inverse association . To our knowledge, only one Japanese cohort study has been conducted including a small number of Asian participants regarding the association between fruit and vegetable intake and pancreatic cancer risk .…”
Section: Introductionmentioning
confidence: 85%
“…[19][20][21][22][23][24][25][26] However, several case-control studies have suggested an inverse association. [27][28][29][30][31][32] To our knowledge, only one Japanese cohort study has been conducted including a small number of Asian participants regarding the association between fruit and vegetable intake and pancreatic cancer risk. 26 Furthermore, the results of previous studies, which have taken into account known risk factors such as obesity and smoking, are inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis [35] reported an inverse relationship between dietary folate intake and pancreatic cancer risk. Additionally, two other case-control studies and several cohort studies observed an inverse relationship [30,31,36,37,38]. The specific mechanism in which folate protects against pancreatic cancer is unknown, however a few are hypothesized.…”
Section: Evidence Linking Dietary Intake To the Pathogenesis Of Pamentioning
confidence: 99%
“…Additional case-control studies completed in China and Italy observed a direct inverse relationship between vegetable consumption and pancreatic cancer [36,41]. However, a Canadian case-control demonstrated an increased intake of fresh fruit and cruciferous vegetables in men only was associated with a 49% reduction in risk [42].…”
Section: Evidence Linking Dietary Intake To the Pathogenesis Of Pamentioning
confidence: 99%